2016
DOI: 10.1007/s11628-016-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-checkout quality on customer satisfaction and repatronage in a retail context

Abstract: Self-service technologies (SSTs) are defined as technological interfaces that enable customers to produce a service without direct employee involvement. Among various SSTs, self-checkouts are being tested by grocery stores across the world. However, while most studies focus on SST adoption, there is limited research on its impact on service quality, customer satisfaction, and retention. Our study investigates consumers' assessments of self-checkout in a retail outlet, and its influence on post-usage intentions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 79 publications
(222 reference statements)
3
62
0
4
Order By: Relevance
“…Furthermore, they varified that high consumer satisfaction results in high consumer loyalty and greater re-purchase intentions (Keiningham, Perkins-Munn and Evans, 2003). In addition, marketing research has shown that the major reason for a consumer's decision to re-purchase a product or re-use intention is his/her level of satisfaction (Anderson and Sullivan, 1993;Kotler and Armstrong, 2010;Fernandes and Pedroso, 2016). Bhattacherjee showed empirically that the level of satisfaction with an IS is a critical factor affecting the continuous use intention of a system (Bhattacherjee, 2001b).…”
Section: Satisfaction and Continuous Use Intentionmentioning
confidence: 99%
“…Furthermore, they varified that high consumer satisfaction results in high consumer loyalty and greater re-purchase intentions (Keiningham, Perkins-Munn and Evans, 2003). In addition, marketing research has shown that the major reason for a consumer's decision to re-purchase a product or re-use intention is his/her level of satisfaction (Anderson and Sullivan, 1993;Kotler and Armstrong, 2010;Fernandes and Pedroso, 2016). Bhattacherjee showed empirically that the level of satisfaction with an IS is a critical factor affecting the continuous use intention of a system (Bhattacherjee, 2001b).…”
Section: Satisfaction and Continuous Use Intentionmentioning
confidence: 99%
“…Source The top-up vending machine is easy to use [9,73] Using top-up vending machine is clear and [9,73] understandable The top-up vending machine does not take [74] much effort…”
Section: Perceived Ease Of Use Itemmentioning
confidence: 99%
“…Retailers increasingly implement checkout terminals in their physical retail environments, which allow customers to quickly scan and pay for products on their own instead of queuing at the cashier desk [7,9,20]. In addition to the speed advantage, researchers involve further attributes to determine the perceived service quality of self-checkouts [23,37]. These attributes include the ease of use, reliability, fun/entertainment, and perceived control.…”
Section: Interactive Technologies and Their Impact On Customer Experimentioning
confidence: 99%
“…Another approach to measuring the service quality of self-checkout systems is to use standard scales, such as the SSTQUAL [22], which consists of seven dimensions (functionality, enjoyment, security, assurance, design, convenience, and customization). Reliability (individual and as a part of functionality) has been identified as a main [22] and even the most important [23,37] driver of the customer's perceived service quality of selfservice checkout technologies. Consequently, service quality positively influences customer loyalty [22], purchase intention [37], intention to reuse [9,38], and repatronage intention [23], directly as well as through the mediating effect of customer satisfaction.…”
Section: Interactive Technologies and Their Impact On Customer Experimentioning
confidence: 99%
See 1 more Smart Citation